Clinico‐epidemiological profile of lichen scrofulosorum: a 22‐year, single‐center, retrospective study. (28th June 2021) - Singal, Archana; Kaur, Ishmeet; Pandhi, Deepika; Gandhi, Vijay; Jakhar, Deepak; Grover, Chander
Abstract: Background: Lichen scrofulosorum (LS) represents immunologic reaction to the Mycobacterium tuberculosis antigen and presents with subtle, asymptomatic, grouped follicular papules over the trunk and shows good therapeutic response to antitubercular drugs. Objective: To study the clinical and epidemiological characteristics of patients diagnosed with LS. Materials and Methods: A single‐center retrospective review of patients diagnosed with LS from 1997 to 2018 was conducted. The data pertained to clinico‐epidemiological profile, BCG vaccination, Mantoux positivity, laboratory investigations, coexistent focus of tuberculosis, and response to antitubercular treatment (ATT). Results: LS cases constituted 15.2% (221/1458) of all the patients diagnosed with cutaneous tuberculosis (CTB). Of these, 156 (70.5%) were pediatric patients. All patients presented with multiple follicular and perifollicular grouped papules. The trunk was the most common site involved (98.6%), followed by lower limb (25.33%), upper limb (15.83%), face (5%), and external genitalia (3.6%). Evidence of BCG vaccination and Mantoux test positivity was observed in 52.03 and 83.2%, respectively. Coexistent TB focus was detected in 134 (60.6%) patients in lymph nodes, lungs, abdomen, and unusual sites such as intracranial, endometrium, and eye. Twenty‐eight patients (12.66%) had coexistent other clinical forms of CTB. Clinical diagnosis of LS was confirmed on histology that revealed chiefly periappendageal epithelioid cell granuloma. Response to ATT was good with complete resolution of lesion in 8–12 weeks. Conclusion: LS appears to be an underdiagnosed entity. Subtle and asymptomatic lesions of LS are often missed, thereby necessitating a high index of suspicion and appropriate evaluation of the underlying TB focus.